Comparing the mechanical properties of additively manufactured post-consumer polypropylene to injection molded specimens. (2022) - Reiter, Martin; Miron, Veronika M.; Lämmermann, Sebastian; Freudenthaler, Paul J.; Jerabek, Michael; Major, Zoltan
Abstract: Single-use plastic applications have resulted in a staggering amount of plastic waste. The total amount of plastic waste was estimated at 80 million tons in 2015, showing an increasing trend. A significant proportion of the total plastic waste is polypropylene (PP). PP offers good mechanical and chemical properties and can be manufactured and molded in a cost- and energy-efficient manner. This amount of plastic waste is forcing society to develop sustainable recycling strategies. For this reason, commercially available PP feedstocks made from post-consumer waste are available for manufacturing. These materials are primarily designed for injection molding or extrusion processes. Additive manufacturing, and in particular material extrusion-based additive manufacturing (ME-AM), has gained significant momentum over the past decade and is already widely used not only for prototyping but also for series production. PP is a material that is typically challenging to process by ME-AM due to its high crystallinity, high shrinkage, and poor adhesion properties. Therefore, this work investigates the use and applicability of PP recyclates in ME-AM. For this purpose, filaments were produced from a commercial grade PP recyclate and tensile specimens were printed with different printing parameters. The mechanical properties were compared to those of injection molded parts and a good relative performance of 64% to 81% was obtained. Although PP seems to be difficult to process with ME-AM, with an optimized print setup and suitable processing parameters, complex parts could be produced.